Cardiovascular risk factors in patients with premature cardiovascular events attending the University of Dresden Lipid Clinic - Schatz, Ulrike; Fischer, Sabine; Müller, Gabriele; Tselmin, Sergey; Birkenfeld, Andreas L.; Julius, Ulrich; März, Winfried; Bornstein, Stefan R. (Atherosclerosis. Supplements, 2019)
Objectives: Despite improved treatment, premature cardiovascular (CV) events remain a major health problem. Aim of this study was to evaluate the patterns of risk factors in patients with premature CV events. Methods: CV risk factors (CVRF) were evaluated in 130 patients with a history of CV events (myocardial infarction, stroke, limb ischemia, stent and bypass intervention in any vessel bed) under 50 years of age attending our lipid clinic. Patients were also stratified according to their Lp(a) concentrations: group 1: 0-45nmol/l (<18mg/dl); group 2: >45-120nmol/l (>18-50mg/dl); group 3: >120nmol/l (>50mg/dl). Results: The most common risk factors in our patients were male sex (75%), current (61%) and previous smoking (9%), arterial hypertension (70%), and a positive family history of early CV events (54%) and hyperlipidemia (69%). Only 27% had a BMI >30kg/m2 and 14% had diabetes mellitus. 69% of patients with premature CV disease (CVD) showed Lp(a) levels>120nmol/l (>50mg/dl). Patients with the highest Lp(a) showed a tendency of more frequent positive family histories of hyperlipidemia. They had experienced their first CV event on average 3 years earlier than those with low Lp(a). CV events predominantly involved coronary arteries. 85% of patients experienced at least one coronary event. Conclusion: In patients with premature CV disease male sex, smoking, hypertension, a positive family history and elevated Lp(a) are the most important CV risk factors. Lp(a) should be considered in the management of young patients with CV disease.